Biofoolish. - Schneider, D.
Of all the possible biofuel crops that can be grown in the United States, perhaps the most attractive is Panicum virgatum, otherwise known as switchgrass. A hardy perennial native to North America, it needs little fertilizer and water, and pests don't seem to like it much. So it holds out the shimmering promise of one day producing vast quantities of fuel in "carbon neutral" fashion, absorbing as much carbon dioxide in growth as it releases when burned. DuPont Danisco Cellulosic Ethanol makes biofuelfrom switchgrass, but the environmental benefits are highly questionable.
Keywords: DuPont Danisco Cellulosic Ethanol; North America; Panicum virgatum; Biofuel crop; Carbon dioxide; Carbon neutral fuel production; Environmental benefits; Switchgrass